A Promising Hard Carbon−Soft Carbon Composite Anode with Boosting Sodium Storage Performance. Issue 19 (2nd October 2020) - Xue, Yanchun; Gao, Mingyue; Wu, Mengrong; Su, Dongqin; Guo, Xingmei; Shi, Jing; Duan, Mengting; Chen, Jiale; Zhang, Junhao; Kong, Qinghong
Abstract: Hard carbon anodes are the most promising candidates for sodium‐ion batteries due to lower sodium‐embedded platform and higher specific capacity. However, pure hard carbon carbons usually show very low initial coulombic efficiency, low electronic conductance, et al . Herein, hard carbon‐soft carbon (HC‐SC) composites composed of carbon nanotubes (CNTs) blooming on porous hard carbon, which were synthesized through thermal decomposition of zeolitic imidazolate framework‐67 (ZIF‐67) and polyvinyl alcohol (PVA) composite. This unique structure could greatly promote the sodium‐ion diffusion and electron transport due to the increased electrode/electrolyte contact area and enlarged pores. As expected, the HC‐SC delivers a high capacity (306.8 mAh g −1 at 500 mA g −1 ), impressive cycling stability (256.8 mAh g −1 after 1000 cycles) and enhanced rate performance (144.9 mAh g −1 at 20 C), which are far superior to those of both individual hard carbon and soft carbon. This encouraging performance may benefit from the synergistic effect of the modified defect concentration and interlayer distance in hard carbon by soft carbon, as well as the unique hierarchical structure. This work provides an exemplary strategy to develop optimized carbon materials for sodium‐ion batteries. Abstract : It's not that hard : Hard carbon‐soft carbon (HC‐SC) composites composed of carbon nanotubes (CNTs) blooming on porous hard carbon are synthesized and used as anodes for sodium‐ion batteries with high performance.